A TRITERPENOID SAPONIN FROM SEEDS OF KOLOWE (Chydenanthus excelsus) - Laode Rijai; Supriyatna Sutardjo; Husein Hernandi Bahti; Unang Supratman; Rymond J. Rumampuk; W.C. Taylor (Indonesian Journal of Chemistry, 2004)
A triterpenoid saponin have been isolated from n-butanol fraction of the seeds of kolowe (Chydenanthus excelsus). The structure was determined as 3-O-[β-D-glucopyranosyl(1→3)-β-D-xylopyranosyl(1→3)- β - D-glucuronopyranosyloxy]- 22α -O-(2-methylbutiroyloxyolean-12-en-15α,16α,28-tri-hydroxy. Structure elucidation was accomplished by NMR (HMBC, HMQC/HSQC, ROE, ROESY, TOCSY) methods, ESIMS, and IR spectroscopic.